DOES INTERNATIONALTOURISTS HAS CAUSALITY EFFECTS WITH ITS FOREIGN DIRECT INVESTMENT AND GROSS DOMESTIC PRODUCT IN INDONESIA? - Muhamad Rifki Fadilah; Riyanto Riyanto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
This study aims to investigate whether the international tourist arrivals affect Tourism FDI and Tourism GDP of Tourism sector in Indonesia during the period 2004 – 2020. In addition, this study also aims to estimate how much and how long the impact of the decline in international tourist arrivals due to the COVID-19 pandemic on the long-term equilibrium between international tourist arrivals, Tourism FDI and Tourism GDP. By using the Granger Causality Test and Vector Error Correction Model (VECM), this study found that the international tourist arrivals affect Tourism FDI and Tourism FDI affects Tourism GDP. Furthermore, the results showed that in the long term, the increase of international tourist arrivals by one percent will increase Tourism FDI by 0.55 percent. Then, one percent increase of Tourism FDI will increase Tourism GDP by 0.10 percent. In the short term (monthly analysis), if there is a